A revision of Taraxacum sect. Atrata, a dandelion group centred in the Middle Asia, and the problem of Taraxacum brevirostre - Kirschner, Jan; Štěpánek, Jan (Phytotaxa, 2017)
The two most primitive Taraxacum sections (Asteraceae, Cichorieae-Crepidinae) in high mountains of Middle Asia and adjacent regions are characterized by almost smooth achenes, frequent absence of discernible cone and a thick beak. One of them, a recently recognized T. sect. Atrata was studied, characterized in detail and its members reviewed. The section is centred in Kyrgyzstan and SE. Kazakhstan and extends to NW. Mongolia in the north, to Pakistan and Ladakh in the southeast and W. China in the east. Eighteen species were found to belong to T. sect. Atrata, nine of them are described as new. All taxa were revised nomenclaturally and the names newly interpreted. Taraxacum sect. Atrata is compared with T. subsect. Epyramidata Orazova (= sect. Oligantha auct.), the other primitive group, also with the highest species diversity in Middle Asia. A special analysis was carried out of T. brevirostre; its syntypes studied and the lectotype described in detail and interpreted as a taxon marginal to T. subsect. Epyramidata.